Teaching during COVID-19: The Decisions Made in Teaching - Liina Lepp; Triinu Aaviku; Äli Leijen; Margus Pedaste; Katrin Saks (MDPI AG, 2021)
The emergency caused by COVID-19 and the transition to distance learning has made teachers face novel decision-making situations. As the teachers' pedagogical decisions have an impact on the students' learning experience, the aim of this study was to describe and explain what influenced the teachers' teaching-related decisions and how these decisions were reflected in the teaching process during distance learning. The study was based on semi-structured interviews with 16 Estonian basic school science teachers. The data were analyzed using qualitative thematic analysis. The results show that teachers' teaching-related decisions were influenced by factors that were related to the existence of digital tools as well as to the ability to use them purposefully in the home settings of teachers and students. Teachers' teaching decisions were mostly motivated by short-term goals, such as maintaining students' social interaction and supporting student motivation. The desire of teachers to keep students' and teachers' own workload affordable was also considered as a factor influencing teachers' teaching-related decisions. According to the interviews, the switch of focus to workload and well-being and valuing socialization and student motivation over subject matter competences seems to be unique for this new situation.